KONSTRUKSI SOSIAL MASYARAKAT TERHADAP ALIRAN TAREKAT NAQSYABANDIYAH DALAM MENYIKAPI PERBEDAAN - Anisa Rusdianasari; Agus Machfud Fauzi (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2022)
Indonesia is one of the countries whose people will believe in God's existence. Indonesian society adheres to various religions, according to what has been recognized by the state, namely 6 religions. Of course there is diversity in one religion. One of them is Islam, in which there are various sects. The Naqsabandiyah Order itself is a sect which is regulated by its adherents as part of Islam, although sometimes it is still a hope in society. These various teachings of Islamic teachings in it may be a pro-contra factor in society. Of course, various speculations about this school will affect its interactions with the surrounding community and views of the community. The research method used is qualitative with a phenomenological approach. Data sourced from interviews and literature review. The research objective here is to analyze and analyze the social construction of the people who know the existence of the Naqsabandiyah Order. The theory used is Peter L. Berger's theory of construction. This theory is used to understand how a certain reality is, so it is suitable for analyzing the phenomenon. The result of this research is that the people in Beduri Village tend to emerge because the sect is deviant because of several teachings and behavior on the road. Society still tends to remain related to the adherents of this sect.